A Meaningful Boost: Effects of Teachers' Sense of Meaning at Work on Their Engagement, Burnout, and Stress - Shiri Lavy (SAGE Publishing, 2022)
The two studies presented here examine the effects of teachers' enhanced sense of meaning at work (SOM) on their burnout and engagement. In the first study, 41 teachers in two Arab schools were randomly assigned to a meaning-induction group-in which they were prompted daily to acknowledge meaningful incidents at work for 2 weeks or to a control group. Qualitative analyses focused on teachers' daily experiences of meaningful incidents, reflecting their contribution to others. In addition, one-way repeated measures analyses of variance indicated that teachers that acknowledged these incidents reported decreased burnout and increased engagement. In Study 2, the sample comprised 60 Arab and Jewish teachers who completed daily surveys for 12 workdays. Hierarchical linear modeling analyses showed that teachers' daily SOM was associated with increased engagement on the following day and somewhat increased stress. Thus, the studies highlight teachers' SOM as a resource that contributes to engagement and can be enhanced intentionally.